ORGANIZATION OF KNOWLEDGE MANAGEMENT IN CONDITIONS OF IMPLEMENTATION OF PROJECT MANAGEMENT IN STATE ADMINISTRATION (Journal of Educational Sciences, 2018)
In the context of the introduction of project management in the public administration, the search for new ways for the effective organization of this process in state bodies and organizations of the Republicof Kazakhstan becomes especially urgent. One of such ways is knowledge management, which consists in applying special organizational methods and forms of training of civil servants aimed at masteringnew knowledge in the field of project management and its implementation in state bodies. For this, the author proposes to create a methodical system for training coaching teams from among teachers, aimedat assisting them in developing competencies in project management, and in organizing modern forms of knowledge management in this field. The purpose of this system is to ensure the harmonization oftraining programs and teaching methods in the field of project management. The article was prepared within the framework of the grant financing of scientific research project of the Ministry of Education andScience of the Republic of Kazakhstan for 2015-2017. No. 3686 / GF4 “Establishment of a post-graduate training system for managers of higher education as a mechanism for developing the intellectual potential of the Republic of Kazakhstan”Key words: knowledge management, project management, civil servants, State management, teachers-trainers.